Jeux de Cartes The Tarot and the Poetry of W.B. Yeats - Giuseppe Serpillo (Studi Irlandesi)
This essay explores the relationship between the Tarot and the poetry of W.B. Yeats. It argues that Yeats was deeply fascinated by the Tarot, and that this fascination is evident in many of his poems. The essay begins by discussing Yeats’s interest in the occult. Yeats was a member of several occult societies, including the Hermetic Society and the Golden Dawn. He was also a friend of Madame Blavatsky, the founder of the Theosophical Society. The essay then goes on to examine the ways in which the Tarot is used in Yeats’s poetry. Yeats often uses Tarot imagery to create a sense of mystery and suspense. He also uses the Tarot to explore themes of love, death, and rebirth. The Tarot provides Yeats with a way to explore the hidden depths of the human psyche. It also helps him to create a poetry that is both beautiful and profound.